Penentuan harga pokok produksi berbasis activity based costing (Studi kasus pada UD Trikora) - Galingging, Sri Karlina; Alexander, Stanly W.; Gerungai, Natalia Y. Telly (Manajemen Bisnis dan Keuangan Korporat, 2025)
An accurate cost measurement system is essential to determine production costs and improve profitability. This research aims to analyse the cost of production of cakalang fish floss at UD Trikora using the Activity Based Costing (ABC) method. The method of analysis used is qualitative with a descriptive approach. The results of this study indicate that the application of the ABC method at UD Trikora in 2023 resulted in a production cost of IDR 136,000.  These results show that the ABC method can identify each activity and its associated costs, enabling the company to allocate costs more accurately. In addition, the application of this method can assist management in determining more competitive pricing strategies. The results of this study are expected to serve as a reference for the company to improve operational efficiency and profitability.